Effects of various levels of dietary fiber on carcass traits, meat quality and myosin heavy chain I, IIa, IIx and IIb expression in muscles in Erhualian and Large White pigs. (November 2020) - Han, Pingping; Li, Pinghua; Zhou, Wuduo; Fan, Lijuan; Wang, Binbin; Liu, Hang; Gao, Chen; Du, Taoran; Pu, Guang; Wu, Chengwu; Zhang, Zongping; Niu, Peipei; et al.
Abstract: This study evaluated the effects of bran fiber levels on carcass traits, meat quality and expression of myosin heavy chain isoform genes in muscles in Erhualian (Er-HL) and Large White pig (LW). Our results showed that fiber level did not affect carcass weight of Er-HL, while carcass weight of LW decreased with the increase of fiber level. Fiber level did not influence meat quality traits of LW, whereas increased fiber level led to an increase in pH45 min of Er-HL, and Er-HL fed 7% bran fiber (BRC) increased redness of meat compared with control diet (CON). We observed a decreased MyHCIIb and MyHCIIx mRNAs and protein levels in Er-HL fed 7% BRC compared with those in other groups, accompanying with a tendency for increased mRNA abundance of MyHCI . The slow-twitch oxidative fiber (MyHCI) is rich in myoglobin and mitochondrial oxidative metabolic enzymes, and the increased expression of MyHCI fiber in pork has resulted in higher redness value. In summary, bran fiber had no adverse effect on the meat quality of LW and appropriate fiber level addition in diets could improve meat quality of Er-HL through regulation the expression of myofiber types. Highlights: Wheat fiber level did not affect the carcass weights of Erhualian. Carcass weights of Large White decreased with the increase of dietary fiber level. Fiber level did not influence meat quality of Large White. 7% wheat bran replaced control diet can improve meat quality of Erhualian. Bran fiber regulated myosin heavy-chain genes expression in muscles of Erhualian.